The Influence of Local Strongman on the Victory of the Roni Omba and Marlinus Couple in the Re-Vote (Study of the 2024 Boven Digoel Regency Election) - Albertina Yuliana Kakbot; Hasanul Bulqiyah (Jurnal Administrasi Publik, 2026)
This study analyzes the influence of local strongmen on the victory of Roni Omba and Marlinus in the revote of Boven Digoel Regency's 2024 Regional Election. Although Petrus Ricolombus Omba was declared ineligible by the Constitutional Court, the consolidated power network successfully maintained massive support through candidate substitution. The research employs a qualitative approach using data from in-depth interviews with key informants, analysis of official documents including Constitutional Court Decision, and Boven Digoel Regency Election Commission's Decision. Main findings reveal that local strongmen's influence operates through four dimensions: kinship networks based on genealogy from two large tribes, patronage systems based on resource distribution and physical presence, spiritual legitimacy integrating religious values as foundation of trust, and regional identity creating significant informal authority. The victory of the Roni Omba-Murtinus pair with 12,990 votes proves that electoral legitimacy is built through long-term trust accumulation, not formal credentials alone. In conclusion, understanding local strongmen is crucial for designing electoral policies sensitive to local socio-cultural realities while strengthening democraticintegrity and honesty principles in electoral administration.